Implementation of Law No. 23 of 2024 concerning Domestic Violence in Karang Suraga Village, Cinangka, Serang, Banten. - Anggriani, Jum; Abdullah, Ali; Arifardhani, Yoyo; Wulan W, Utji Sri (PT Inovasi Pratama Internasional, 2024)
This study analyzes the implementation of Law No. 23 of 2004 concerning the Elimination of Domestic Violence (KDRT) in Karang Suraga Village, Cinangka, Serang, Banten. The main focus of the study is to identify the effectiveness of the implementation of the law in the context of a village community that still strongly adheres to a patrilineal system. Using a qualitative approach with a normative-empirical legal research method, this study combines analysis of legal aspects and social realities in the field. Data collection was conducted through in-depth interviews with community leaders, law enforcement officers, victims of domestic violence, and village officials, and supported by non-participant observation and documentation studies. The results of the study indicate that the implementation of the Domestic Violence Law in Karang Suraga Village still faces significant challenges rooted in patriarchal cultural factors, socio-economic conditions, and the level of community education. Although the village government has established a complaint and family counseling post, its effectiveness is hampered by the view of the community that still considers domestic violence as a family disgrace. The identified impacts of domestic violence include prolonged trauma for victims and negative effects on child development. This study recommends the importance of a comprehensive approach that combines legal aspects with socio-cultural transformation to create sustainable change in efforts to eliminate domestic violence at the village level.